Application of human iPSC-derived white, beige, and brown adipocytes for metabolic disease modeling and transplantation therapy - Yamato Keidai; Junji Fujikura; Daisuke Yabe (Cell Transplantation)
Adipocyte dysfunction plays a critical role in the pathogenesis of metabolic diseases, including type 2 diabetes (T2D). Human induced pluripotent stem cells (hiPSCs) offer a powerful platform for generating white, beige, and brown adipocytes, supporting both disease modeling and therapeutic research. This review provides a comprehensive summary of current differentiation methods to produce three functionally mature adipocyte types from pluripotent stem cells (PSCs), including forced gene expression techniques, developmental biology-inspired approaches, and advanced three-dimensional (3D) culture systems that enhance cellular maturity and functional relevance. PSC-derived white adipocytes contribute to modeling adipocyte dysfunction not only in conditions such as insulin resistance, lipodystrophy, and premature aging but also in more complex metabolic diseases, including T2D, facilitating the investigation of disease mechanisms and the identification of novel therapeutic targets. In addition, iPSC-based models provide a robust platform for exploring genetic regulation by genome-wide association studies (GWAS)–identified variants through population genetics. This review also evaluates the therapeutic potential of iPSC-derived white, beige, and brown adipocytes in cell transplantation therapy for metabolic diseases, with a focus on engraftment potential and metabolic improvement. Enhancing the maturity and subtype specificity of PSC-derived adipocytes is expected to accelerate the development of personalized medicine and innovative therapeutic strategies for metabolic diseases.